1997
DOI: 10.1104/pp.115.2.643
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose and Callose Biosynthesis in Higher Plants (I. Solubilization and Separation of (1->3)- and (1->4)-β-Glucan Synthase Activities from Mung Bean)

Abstract: (1 +3)-and (1 +4)-P-glucan synthase activities from higher plants have been physically separated by gel electrophoresis in nondenaturing conditions. The two glucan synthases show different mobilities i n native polyacrylamide gels. Further separation by sodium dodecyl sulfate-polyacrylamide gel electrophoresis revealed a different polypeptide composition i n these synthases. Three polypeptides (64, 54, and 32 kD) seem to be common to both synthase activities, whereas two polypeptides (78 and 38 kD) are associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(65 citation statements)
references
References 54 publications
2
63
0
Order By: Relevance
“…Independently, Arioli et al (1998) found the same gene using an Arabidopsis mutant. Kudlicka and Brown (1997) reported the separation of ␤ -1,3-and ␤ -1,4-glucan synthase activities using gel electrophoresis in nondenaturing conditions. These gels could be incubated in UDP-glucose and the resulting in vitro products visualized with the electron microscope.…”
Section: Resultsmentioning
confidence: 99%
“…Independently, Arioli et al (1998) found the same gene using an Arabidopsis mutant. Kudlicka and Brown (1997) reported the separation of ␤ -1,3-and ␤ -1,4-glucan synthase activities using gel electrophoresis in nondenaturing conditions. These gels could be incubated in UDP-glucose and the resulting in vitro products visualized with the electron microscope.…”
Section: Resultsmentioning
confidence: 99%
“…This unique pollen tube wall structure is thought to allow faster growth rates than possible in other tip-growing cells because (i) the pectic tip is more plastic and rapidly extensible, (ii) the mature tube cell wall has greater resistance to tension stress because of deesterification of pectins and secretion of callose, and (iii) callose plugs help maintain positive turgor pressure in the growing tip (27,31). There is evidence that building an amorphous callose-based wall is faster and more energy efficient than biosynthesis of a cellulose microfibril-based wall (29,32). Furthermore, silencing of genes involved in either pectin modification or callose synthesis reduces pollen competitive ability (33-35).…”
Section: Relationship Between Pollen Tube Growth and Carpel Evolutionmentioning
confidence: 99%
“…The first successful in vitro synthesis of cellulose from plant cell-free extracts was achieved using cotton fiber and mung bean (Vigna radiata) enzymes (Kudlicka et al, 1995(Kudlicka et al, , 1996Kudlicka and Brown, 1997). However, it was only several years later that the amount of cellulose synthesized in vitro was significantly improved by the careful selection of detergents that allow the extraction of enzyme complexes in an intact form (Lai Kee Him et al, 2002).…”
Section: Biochemical Analyses Of Cellulose Biosynthesismentioning
confidence: 99%